If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -4 + -5x = -8 Reorder the terms: -4 + 4x + -5x = -8 Combine like terms: 4x + -5x = -1x -4 + -1x = -8 Solving -4 + -1x = -8 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + -1x = -8 + 4 Combine like terms: -4 + 4 = 0 0 + -1x = -8 + 4 -1x = -8 + 4 Combine like terms: -8 + 4 = -4 -1x = -4 Divide each side by '-1'. x = 4 Simplifying x = 4
| -0.1=5.1+2y | | 11(c-5)+4=3+c-54 | | 6p=164 | | 4g+3(-8+3g)=1-g | | 2(2t-3)=6t+2 | | -15+2k=k-4k | | 5p-3p=51 | | 7x+2-9x=10+2x | | 4+(3-3x)-(1-x)=4x-2(x-3) | | 2x-1=75 | | 5-5x=2-8x | | 4x+13=-9-(3x+9) | | 6(1+3n)-8(6n+12)=-n-11n | | 7b-19=2b+1 | | -15=3(3x+1) | | 4(y+6)=5(y-8) | | 3(13+2d)-7=13-(12+2d) | | -21=7(y+2) | | 3-4q=10+10q | | X-3+14=5 | | -3.1x=7.75 | | 4z+17=3z+6 | | 8(w-3)=40 | | 8x-(4x+9)= | | 4-5x=-6 | | 4y+4=3y-9 | | (15+x)+(17+x)=72 | | -6a+3=-3(2a-q) | | -32+8+(-22)=-12 | | 7x+4x=68 | | -9y-12=5y+16 | | 2x(54)=7 |